Dress and identity in Iron Age Britain : a study of glass beads and other objects of personal adornment - Foulds, Elizabeth Marie, (Archaeopress archaeology., 2017)
Through an analysis of glass beads from four key study regions in Britain, the book explores the role that this object played within the networks and relationships that constructed Iron Age society.